Evaluation of Wound Healing Activity (Excision Wound Model) of Ointment Prepared from Infusion Extract of Polyherbal Tea Bag Formulation in Diabetes-Induced Rats. (6th June 2022) - Quazi, Aamir; Patwekar, Mohsina; Patwekar, Faheem; Mezni, Amine; Ahmad, Irfan; Islam, Fahadul
Abstract : In the present investigation, Ichnocarpus frutescens, Ficus dalhousiae, Crateva magna, Alpinia galanga, and Swertia chirata plants were selected to formulate polyherbal tea bag. The infusion obtained from these polyherbal tea bags was used to formulate 5% and 10% ointment formulation to perform its wound healing activity. The excision wound model was used to assess the wound healing activity in diabetic as well nondiabetic rats. The mean percentage closure of wound area was calculated on the 3 rd, 6 th, 9 th, 12 th, 15 th, 18 th, and finally 21 st day. The wound healing activity of formulation was found to be significantly compared with that of the reference standard and untreated groups. The percentages of closure of excision wound area on the 21 st day in diabetic animals treated with ointment formulations (F1 and F2) were found to be 93.91 ± 1.65% and 99.12 ± 5.21% respectively, whereas the chloramphenicol sodium drug solution was found to be 99.81 ± 3.16%. The percentages of closure of excision wound area in nondiabetic animals treated with ointment formulations (F1 and F2) were found to be 96.81 ± 2.04% and 98.13 ± 1.14%, respectively, whereas the chloramphenicol sodium drug solution was found to be 99.15 ± 1.41% at 21 st day. Therefore, from the above results, we have concluded that this polyherbal ointment can be used clinically for the treatment of diabetic and nondiabetic wounds.